Outcomes of Endovascular Therapy for Salvage of Hemodialysis Arteriovenous Fistulae - Nishtha Yadav; Shivanand Gamanagatti; Raju Sharma; Sanjay Kumar Aggarwal; V. K. Bansal; Devasenathipathy Kandasamy; V. Seenu (Journal of Clinical Interventional Radiology ISVIR)
Introduction Arteriovenous fistulae (AVF) for hemodialysis (HD) are prone to development of multiple complications, which can lead to nonfunctioning of the fistula. We report outcomes of endovascular management for dysfunctional HD AVF. Materials and Methods In this prospective study, patients (43 men, 28 women, mean age 47.4 years) with clinical signs and symptoms of dysfunctional HD AVF and referred to interventional radiology for endovascular management were included. The most common clinical presentation included low flows during hemodialysis (n = 20), absent flow (n = 37), and failure of fistula maturation (n = 14). Patients with central venous obstruction who presented with limb swelling were excluded from this study. Patients underwent venography, venoplasty and thrombectomy, as appropriate, to salvage the fistula. The study outcomes were technical success, hemodynamic success, and clinical success of endovascular therapies in salvaging the fistulae. Results The technical, hemodynamic and clinical success rates of endovascular therapy for low-flow symptoms were 95%, 70% and 95%, respectively. Among patients who presented with absent flow, endovascular therapy had 81% technical success, 78.3% hemodynamic success, and 81% clinical success. Endovascular therapy was associated with 64.2% technical success, 57.1% hemodynamic success, and 64.2% clinical success in patients presenting with failed maturation of the fistula. The overall clinical success rate was 58/71 (81.7%) and failure rate was 13/71 (18.3%). The overall complication rate of endovascular therapy was 8.4% and the complications included vein rupture in 5 (7%) and balloon rupture in 1 (1.4%). Conclusion Endovascular therapy for salvage of nonfunctioning hemodialysis AVF is associated with a high-clinical success rate (81.7%) and low-complication rate.